2015
DOI: 10.1017/s1431927614014093
|View full text |Cite
|
Sign up to set email alerts
|

Multi-analytical characterization of paper samples exhibiting foxing stains

Abstract: Deterioration of graphical documents can occur naturally as a result of aging, but it can be accelerated by poor manufacturing constituents or conditions. One indicator of deterioration can be discoloration or staining of the surface [1][2][3]. Among these paper discoloration processes is foxing, which has been actively researched since the 1930s. Our attention herein is focused on trying to elucidate its causes and to establish protocols for detection, prevention and treatment. This foxing phenomenon occurs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…These two images show similar features of nanoparticle size and distribution, they complement each other and demonstrate that the development and formation of image nanoparticles is greatest immediately below the surface and down to about 1 to 2 μ m deep, then the particle concentration decreases with depth into the paper matrix. In this study the particles have been observed down to about 10 μ m, and this is comparable with the depth value of 15 μ m reported by Stulik & Kaplan (2013).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These two images show similar features of nanoparticle size and distribution, they complement each other and demonstrate that the development and formation of image nanoparticles is greatest immediately below the surface and down to about 1 to 2 μ m deep, then the particle concentration decreases with depth into the paper matrix. In this study the particles have been observed down to about 10 μ m, and this is comparable with the depth value of 15 μ m reported by Stulik & Kaplan (2013).…”
Section: Discussionsupporting
confidence: 91%
“…As expected, a greater number of particles are seen toward the top of the paper’s surface and can also be found deep within the paper’s fibers up to a depth of 10 μ m below the surface. Stulik and Kaplan (2013) also noted that image particles could be found as deep as 15 μ m. In the high-resolution BE image of Figure 1f1, one observes what appears to be a preferential deposition of the image particles within a fiber and its inner layers. The bulk of image particles are deposited directly beneath the fiber surface in the primary wall, then between the primary (P) wall and outer secondary (S1) wall, and between other more internal walls as seen in the cutaway diagram of a paper fiber in Figure 1f2.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations